Clustering of Regencies in Kalimantan Barat Based On Community Welfare Indicators - Wahyudio Hariadi; Shantika Martha; Desa Ayu Natalia (Badan Pusat Statistik Provinsi Kalimantan Barat, 2024)
Welfare is the capacity to meet all life's necessities to live decently, healthily, and productively. The objective of this study is to classify districts/cities in Kalimantan Barat Province according to indicators of community welfare. The data utilized include the percentage of impoverished individuals, gross regional domestic product, average years of schooling, expected years of schooling, and life expectancy. The procedure in this study commenced with a descriptive analysis of each variable, followed by the formation of an Euclidean distance matrix. After that, clustering with the centroid linkage method, in this case using the value of the silhouette coefficient to determine the optimal number of clusters formed. The clusters' outcomes are visible in the dendrogram. Cluster traits are identified based on the mean value of each variable within each cluster. The findings of the analysis indicate that Kota Pontianak enjoys high welfare, while the other thirteen districts are classified as having low welfare levels.